Effect of Jagged-1 and Dll-1 on osteogenic differentiation by stem cells from human exfoliated deciduous teeth. (May 2016) - Sukarawan, Waleerat; Peetiakarawach, Karnnapas; Pavasant, Prasit; Osathanon, Thanaphum
Highlights: The Dll-1 and Jagged-1 immobilized surface were able to activate Notch signaling in SHEDs. ALP activity and mineralization were significantly increased in those cells seeded on Jagged-1 immobilization surface. High concentration of Dll-1 immobilization slightly enhanced alkaline phosphatase enzymatic activity in SHEDs. Jagged-1 had more ability in enhancing osteogenic differentiation than Dll-1. Abstract: Objective: The aim of the present study was to determine the influence of Notch ligands, Jagged-1 and Dll-1, on osteogenic differentiation by stem cells from human exfoliated deciduous teeth. Design: Notch ligands were immobilized on tissue culture surface using an indirect affinity immobilization technique. Cells from the remaining of dental pulp tissues from human deciduous teeth were isolated and characterized using flow cytometry and differentiation assay. Alkaline phosphatase (ALP) enzymatic activity, osteogenic marker gene expression, and mineralization were determined using ALP assay, real-time polymerase chain reaction, and alizarin red staining, respectively. Results: The isolated cells exhibited CD44, CD90, and CD105 expression but lack of CD45 expression. Further, these cells were able to differentiate toward osteogenic lineage. The upregulation of HES-1 and HEY-1 was observed in those cells on Dll-1 and Jagged-1 coated surface. The significant increase of ALP activity and mineralization was noted in those cells seeded on Jagged-1 surface and these results were attenuated when cells were pretreated with gamma secretase inhibitor. The significant upregulation of ALP and collagen type I gene expression was also observed in those cells seeded on Jagged-1 surface. The inconsistent Dll-1 induced osteogenic differentiation was found and high Dll-1 immobilized dose (50 nM) slightly enhanced alkaline phosphatase enzymatic activity. However, the statistical significant difference was not obtained as compared to the hFc control. Conclusion: The surface immobilization of Notch ligands, Jagged-1 and Dll-1, likely to enhance osteogenic differentiation of SHEDs. However, Jagged-1 had more ability in enhancing osteogenic differentiation than Dll-1 in our model.